Beberapa Pandangan Pengembangan Pasar Modal di Indonesia - ., Sunarjanto (Responsibilitas, 2010)
Abstract In reaching purpose of long-range development, that is chartered investment counsel area is how compilation a chartered investment counsel structure, either in agricultural sector and also industry, to earn together becomes first bollard of prosperity and prosperity flattening for Indonesian nation. Role and participation of the entrepreneurs and private company hardly determines. Related to it stock market and Indonesia stock exchange is one of source of development potency of national corporate world. With the entry of national corporate world to open Indonesia Stock Exchange of possibility for him to grow health and proper, because supported by public fund. By growing it corporate world, means field work increasingly open wide. Referring to the matter the investors and government have interest to depress the risk as small as possible without pursuing mechanism of itself stock market. Keyword: Pasar Modal, Pengembangan